A novel 2-D Mn selenidostannate(iv) incorporating high-nuclear Mn clusters with spin canting behavior. Issue 46 (9th November 2017) - Zhou, Jian; Xiao, Hong; Zou, Hua-Hong; Liu, Xing
Abstract : The incorporation of a hepta-nuclear Mn cluster [Mn7 (ea)6 ] 8+ into a selenidostannate(iv ) framework leads to a novel 2-D Mn selenidostannate(iv ) with spin canting behavior. Abstract : A solvothermal reaction of SnCl4 ·5H2 O, Mn and Se in ethanolamine (Hea) yielded a novel 2-D Mn selenidostannate(iv ) [Mn7 (ea)6 (SnSe4 )2 ] n (1 ), which not only provides the first example of the incorporation of a hepta-nuclear Mn cluster [Mn7 (ea)6 ] 8+ into a selenidostannate(iv ) framework, but also shows unusual spin canting behavior.